THE STUDENTS’ INTEREST IN USING DUOLINGO AS A LEARNING MEDIA IN SPEAKING - Firmansyah; Anugrawati, Nunung; St. Asmayanti AM (Journal of Computer Interaction in Education, 2021)
This research aims to find out the students’ interest in using an app called Duolingo as their speaking learning media at eighth grade of SMPN 1 Galesong Utara in Academic Year 2021/2022. The sample of this research used 30 students from eight grade and the sample was taking by using Random Sampling technique. The approach of this study is Descriptive Qualitative. The instrument that use to collect the data was questionnaire with five option likert. Based on the findings, the researcher said that the students in SMPN 1 Galesong utara are “interested” to use Duolingo as their learning media. This can be proved by the students questionnaire result, that showed magnificent score, with classification “interested” (2.51 – 5.00), and the average score that the students’ got was 3.9. Therefore, the conclusion of the research is the students’ in SMPN 1 Galesong Utara are interested in using Duolingo as their media in learning speaking